2016
DOI: 10.1016/j.rmcr.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse cystic lung disease due to pulmonary metastasis of colorectal carcinoma

Abstract: The diffuse cystic lung diseases (DCLDs) are a pathophysiologically heterogeneous processes characterized by the presence of multiple thin-walled, air-filled spaces within the pulmonary parenchyma. The most common causes of DCLD are lymphangioleiomyomatosis (LAM) and pulmonary Langerhans cell histiocytosis (PLCH).DCLD develops rarely as a result of malignancy, typically secondary to metastases from peripheral sarcomas and mesenchymal tumors. DCLD have also been reported in a variety of other metastatic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Pulmonary nodules and cysts are also characteristic of pulmonary Langerhans cell histiocytosis; however, it can be distinguished from pulmonary LCDD by its upper-lung-predominant distribution of pulmonary findings, the presence of cavitary nodules, and the differing clinical context in which it occurs (predominantly affects young adult smokers) [19,20]. Patients with malignancy rarely present with cystic and solid pulmonary metastases, but similar scenarios have been described in angiosarcoma, colorectal adenocarcinoma, and benign metastasizing leiomyoma [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary nodules and cysts are also characteristic of pulmonary Langerhans cell histiocytosis; however, it can be distinguished from pulmonary LCDD by its upper-lung-predominant distribution of pulmonary findings, the presence of cavitary nodules, and the differing clinical context in which it occurs (predominantly affects young adult smokers) [19,20]. Patients with malignancy rarely present with cystic and solid pulmonary metastases, but similar scenarios have been described in angiosarcoma, colorectal adenocarcinoma, and benign metastasizing leiomyoma [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory biomarkers: Inflammatory markers, such as C-reactive protein and cytokines, can be elevated in DCLDs and may provide insights into the inflammatory processes occurring in the lungs. [35] It important to note that the field of DCLD biomarkers is still evolving, and further research is needed to validate and refine these biomarkers for diagnostic and prognostic purposes. The The discovery that the majority (92%) of ALK-positive lesions are solid tumors aligns with previously reported CT and histological findings of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LMCC with multiple cavitary lung lesions may be misdiagnosed as an infection. Notably, all three reported cases of LMCC with multiple cavitary lung lesions were initially diagnosed as infections [ 2 , 7 , 8 ]. In a study of 102 patients with multiple cavitary lung lesions, 73 (71.6%) were diagnosed with infection and 20 (19.6%) with lung metastases, and this study showed that a greater number of cavitary lesions and the absence of centrilobular nodules were associated with a higher probability of malignancy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung metastasis with cavitary lesions is rare [ 1 ]. It is sometimes misdiagnosed as an infection, leading to a poor prognosis [ 2 ]. We report a case of multiple cavitary lung metastases from colorectal cancer that responded to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%